The SLCO1B1*15 haplotype associated with lower clinical outcome in Indonesian tuberculosis patients - Sunarto Ang; Akhmad Kharis Nugroho; Ahmad Hamim Sadewa; Lukman Hakim; . Mustofa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Rifampin is one of first-line drugs for the treatment of tuberculosis. In Indonesia nearly alltuberculosis patients show lower rifampin plasma concentrations possibly due to genetics.Rifampin is a substrate of the organic anion-transporting polypeptide 1B1 (OATP 1B1)encoded by the solute carrier organic anion transporter family member 1B1 (SLCO1B1).This study aimed to identify haplotype polymorphisms of tuberculosis drug transporterswith an impact on clinical outcome in tuberculosis patients. Thirty-six patients from AbdulWahab Sjahranie General Hospital, Samarinda, East Kalimantan were involved in thestudy. Buffy coat from patient blood samples were tested for SLCO1B1 and SLCO1B3polymorphisms by RFLP and ARMS PCR, whereas the clinical outcome was examinedbased on the sputum conversion. The frequency of patients with SLCO1B1*15 haplotypewas 63.9%. The SLCO1B1*15 haplotype was associated with susceptibility to failureof clinical outcome (p=0.005; RR=4.52; 95% CI: 1.22-16.64). The OATP1B1*15haplotype revealed that the failure of clinical outcome was markedly increased comparedto the three other haplotypes. These results suggest that the SLCO1B1*15 haplotypeis an important predisposing factor for lower clinical outcome. Our data indicate thatindividualized treatment should be considered for Indonesian tuberculosis patients basedon genetics characteristics of patients.